2018
DOI: 10.1002/ppap.201800135
|View full text |Cite
|
Sign up to set email alerts
|

Growth of nanocolumnar thin films on patterned substrates at oblique angles

Abstract: The influence of one dimensional substrate patterns on the nanocolumnar growth of thin films deposited by magnetron sputtering at oblique angles is theoretically and experimentally studied. A well-established growth model has been used to study the interplay between the substrate topography and the thin film morphology. A critical thickness has been defined, below which the columnar growth is modulated by the substrate topography, while for thicknesses above, the impact of substrate features is progressively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This is a well‐known phenomenon in surface shadowing‐mediated growths, where the competition among nanocolumns is responsible for either the inhibition of the growth of shorter nanocolumns or their progressive merging with neighboring ones. [ 16 ] This structural evolution with thickness is confirmed by the HAADF‐STEM image in Figure 2a. This technique, for a given material composition, provides an estimation of the amount of material through the slice under analysis and shows the same nanocolumnar structure as in Figure 1a, with the same tilt angle and columnar thickening with height.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This is a well‐known phenomenon in surface shadowing‐mediated growths, where the competition among nanocolumns is responsible for either the inhibition of the growth of shorter nanocolumns or their progressive merging with neighboring ones. [ 16 ] This structural evolution with thickness is confirmed by the HAADF‐STEM image in Figure 2a. This technique, for a given material composition, provides an estimation of the amount of material through the slice under analysis and shows the same nanocolumnar structure as in Figure 1a, with the same tilt angle and columnar thickening with height.…”
Section: Resultsmentioning
confidence: 55%
“…[13,14] Its fundamentals rely on the same ideas accounting for the evaporation technique at glancing angles, [15] where gaseous deposition species are made to arrive at a substrate along a certain preferential oblique direction, inducing surface shadowing mechanisms and promoting a selforganization phenomenon that gives rise to nanocolumnar arrays. [13,16] Interestingly, these nanocolumns are far from being structurally homogeneous: in Reference [14] for instance, it was demonstrated that W nanocolumns presented clear morphological inhomogeneities, with the side facing the target being smooth and highly compact while the opposite one was fibrous with numerous protuberances. In this paper, we aim at analyzing the stoichiometric variations when the growth takes place in the presence of reactive gas (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, compositional patterning will remain wherever a clear topographic pattern is preserved. In a recent investigation on this question we have found that the topography of a substrate pattern affect the microstructure of thin films deposited by magnetron sputtering at oblique angles until a certain characteristic oblivion thickness that is in the order of the separation between pattern strips [33]. The previous experiments clearly demonstrate that the combination of r-MS-OAD and rippled substrates is straightforward for the 2D self-patterning of thin film composition over the substrate surface.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…To maximize the performance for water splitting, electrodes must present a high porosity and a large electrochemical active surface area [122]. The OAD-MS technique permits the fabrication of highly porous electrodes consisting of nanocolumns separated by large voids [115,123]. This nanocolumnar microstructure stems from atomic shadowing effects taking place during the electrode growth [124][125][126].…”
Section: Magnetron Sputtering Depositionmentioning
confidence: 99%